2019
DOI: 10.1136/jmedgenet-2018-105669
|View full text |Cite
|
Sign up to set email alerts
|

Genetic linkage analysis of a large family identifies FIGN as a candidate modulator of reduced penetrance in heritable pulmonary arterial hypertension

Abstract: BackgroundMapping the genetic component of molecular mechanisms responsible for the reduced penetrance (RP) of rare disorders constitutes one of the most challenging problems in human genetics. Heritable pulmonary arterial hypertension (PAH) is one such disorder characterised by rare mutations mostly occurring in the bone morphogenetic protein receptor type 2 (BMPR2) gene and a wide heterogeneity of penetrance modifier mechanisms. Here, we analyse 32 genotyped individuals from a large Iberian family of 65 memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…2 The current patient had previously reported pathogenic variant in BMPR2: c.1472 G > A (p.Arg491Gln) located in a kinase domain. 3 The missense heterozygous variant is predicted to be disruptive based on the alteration and interaction of protein structure, although the functional mechanism has yet to be clarified. 4 The epigenetic mechanism may also contribute to the genetic bases for the etiopathogenesis of PAH, because the COVID-19 pandemic is known to be associated with PAH.…”
Section: Discussionmentioning
confidence: 99%
“…2 The current patient had previously reported pathogenic variant in BMPR2: c.1472 G > A (p.Arg491Gln) located in a kinase domain. 3 The missense heterozygous variant is predicted to be disruptive based on the alteration and interaction of protein structure, although the functional mechanism has yet to be clarified. 4 The epigenetic mechanism may also contribute to the genetic bases for the etiopathogenesis of PAH, because the COVID-19 pandemic is known to be associated with PAH.…”
Section: Discussionmentioning
confidence: 99%
“…Two of these genes, HTRA3 and STAC2 , were found as the top five hypermethylated CGIs in primary tumour and LNM, respectively. FIGN (fidgetin) is a gene coding for a microtubule severing enzyme as well as a depolymerase, predominantly involved in mitosis but also contributing to cell migration and neuronal development [ 46 ]. Studies have shown that FIGN is overexpressed in human hepatocellular carcinomas promoting hepatocyte invasion [ 47 ] HTRA3 (high temperature requirement A3) is a member of the HtrA family and is a proapoptotic protease shown to promote drug-induced cytotoxicity and proposed to have an antitumour effect [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fidgetin may play a cardioprotective role through a non‐severing function according to recent evidence. Multiple human single nucleotide polymorphisms (SNPs) associated with cardiorespiratory phenotypes and with heritable pulmonary arterial hypertension have been identified in the distal promoter region of the fidgetin gene, leading to less penetrance of the gene mutation responsible for heritable pulmonary arterial hypertension (Puigdevall et al, 2019). Studies with Han Chinese populations indicated three isoforms of fidgetin, one of which—X3—was associated with lower risk of congenital heart defects when it contained a +94762G>C SNP (D. Wang, Chu, et al, 2017).…”
Section: Roles In Tissue Function and Dysfunctionmentioning
confidence: 99%